Modelling of Water Front Advance under Surge Furrow Irrigation - Babu, R Ravi; Rajput, TBS; Bhattacharya, A K; Mishra, Purnima (Journal of Agricultural Engineering, 2005)
A Surge flow furrow irrigation computer model was developed to simulate the water front advance trajectories for given surge cycle on and off times based on the kinematic-wave theory. Iinfiltration under surge furrow irrigation was assumed to be in three phases namely dry, transition and wet phases. Field data from the sandy-loam soil of the research farm of W.T.C, IARI were used to verify the model’s simulations. The kinematic-wave model could effectively simulate the advance of water front under surge flow furrow irrigation. The model could be used as an effective tool in designing surge flow furrow irrigation system.